A study of the implementation factors of end-life-vehicle policy - Nur Anis Izzaty Zainuddin; Norashikin Samuri; Muhamad Razuhanafi Mat Yazid; Rozmi Ismail; Rosniza Aznie Che Rose; Zurinah Tahir; Nur Atiqah Suparjo Noordin; Charli Sitinjak (Penerbit Universiti Kebangsaan Malaysia, 2024)
Vehicles with a lifespan exceeding 10-15 years are classified as End-of-Life Vehicles (ELV). Since widespread use of ELV could potentially pollute the environment, it is essential to formulate an ELV management framework to deal with this issue. This study aims to understand the laws related to ELV, study its implementation in other countries and measure public opinion concerning implementing ELV recycling in Malaysia. Therefore, the study surveyed 200 respondents and analysed the data using the Statistical Package Software for Social Sciences (SPSS). The results showed that the employment sector and estimated income significantly influenced knowledge of solid waste management and end-of-life vehicles, community readiness and community attitude, with a value of 0.001 (less than 0.005). The results revealed that most respondents (68.5%) agreed with the ideas concerning ELV, while 31.5% disagreed. The researcher concludes the study with recommendations to the relevant parties, including the government, to improve the final vehicle policy life before its full implementation.